2011
DOI: 10.1007/s00170-011-3558-1
|View full text |Cite
|
Sign up to set email alerts
|

Process parameters selection for laser polishing DF2 (AISI O1) by Nd:YAG pulsed laser using orthogonal design

Abstract: Mechanisms of laser polishing metals in a continuous scanning mode, as envisaged and analyzed in this paper, are rather complex, and experimental optimization of laser polishing metallic material is very timeconsuming and difficult. Aiming at shortening the experimental time in achieving a better surface finishing of DF2 (AISI 01) tool steel by pulse Nd:YAG laser, we used the orthogonal experimental design for selecting the laser operational parameters. The results showed that the orthogonal design (OD) allowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…The effects of process parameters such as energy density [17][18][19], scanning speed [20] and step-over distance [21] on the quality of laser polished surfaces have been studied by numerous researchers, with the majority concluding that laser energy density has the strongest influence on resulting surface integrity [19]. Laser energy density is typically controlled by varying the focal offset distance (FOD) from the workpiece, which correspondingly alters the diameter of the beam.…”
Section: Laser Polishing Of Steel and Cast Ironmentioning
confidence: 99%
“…The effects of process parameters such as energy density [17][18][19], scanning speed [20] and step-over distance [21] on the quality of laser polished surfaces have been studied by numerous researchers, with the majority concluding that laser energy density has the strongest influence on resulting surface integrity [19]. Laser energy density is typically controlled by varying the focal offset distance (FOD) from the workpiece, which correspondingly alters the diameter of the beam.…”
Section: Laser Polishing Of Steel and Cast Ironmentioning
confidence: 99%
“…For example, Mai and Lim [118] applied laser polishing to reduce the roughness of 304 stainless steel from 195 nm to 75 nm, consequently increasing surface reflectivity to 14% and reducing diffusion reflectivity to 70%. Guo et al [119] investigated polishing results in AM processes, showing that the roughness value decreased from 0.4 µm to 0.12 µm. Lamikiz et al [120] claimed that the hardness of a laser polishing processed surface was slightly higher and more uniform than other surfaces, with almost no cracks or HAZ.…”
Section: Laser Polishingmentioning
confidence: 99%
“…Feed rate in lasers means pulses per millimeter. The peaks on the metal surfaces are removed using the laser irradiation where an improper speed can result in a rough surface instead of a smoother one [48]. Previous works showed that higher feed rates above a certain limit lead to a rougher surface and poor surface finish which is evident from Fig.…”
Section: Feed Ratementioning
confidence: 99%